Taking science to cholera in Bangladesh: the personal odyssey of Dr William B Greenough III and his colleagues - Niloufar Shababi; Sanaz Nourmohammadi Abadchi; William B Greenough (eGastroenterology)
Cholera is one of the most rapidly fatal infectious diseases known. Historically, two major problems have been faced by those who care for patients with cholera: first, how to treat individual patients to prevent rapid death, and second, how to prevent the spread of this highly contagious disease in the immediate community and beyond. In this review, we will discuss how clinical scientists have approached these two issues with some personal experiences that Dr William B Greenough III encountered when he was addressing these problems and treating cholera victims at the Pakistan SEATO Cholera Research Laboratory in the early 1960s in Dhaka, East Pakistan.